2016
DOI: 10.1016/j.jpsychires.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Problematic internet use (PIU): Associations with the impulsive-compulsive spectrum. An application of machine learning in psychiatry

Abstract: Problematic internet use is common, functionally impairing, and in need of further study. Its relationship with obsessive-compulsive and impulsive disorders is unclear. Our objective was to evaluate whether problematic internet use can be predicted from recognised forms of impulsive and compulsive traits and symptomatology. We recruited volunteers aged 18 and older using media advertisements at two sites (Chicago USA, and Stellenbosch, South Africa) to complete an extensive online survey. State-of-the-art out-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(55 citation statements)
references
References 47 publications
4
50
0
1
Order By: Relevance
“…Several studies showed the negative effects of bedtime blue light-emitting-device use on sleep due to its association to cognitive stimulation [1,4,6,7,[14][15][16][17][18] and/or to problematic excessive use [9,[18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed the negative effects of bedtime blue light-emitting-device use on sleep due to its association to cognitive stimulation [1,4,6,7,[14][15][16][17][18] and/or to problematic excessive use [9,[18][19][20][21][22][23][24][25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, there is an emergent problematic and worrying excessive use of these new technologies in people of all ages reported by several studies [9,[18][19][20][21][22][23][24][25][26][27][28]. As we are all conscious of bedtime, wake time and the subjective quality of sleep, our appreciation of the importance of the sleep-wake cycle should be further enhanced when confronted with the consequences of its disruption [29].…”
Section: Introductionmentioning
confidence: 99%
“…19 The current study extends beyond this prior meta-analysis by also considering the impact of study quality, and including a much larger range of available data. Problematic internet users are characterised by elevated behavioural impulsivity and compulsivity, 11,15 which are characteristics of a wide range of psychiatric disorders, including ADHD, OCD, impulse control and substance use disorders.…”
Section: Comparison With Findings From Other Studiesmentioning
confidence: 99%
“…12 Based on empirical evidence, we define PIU as excessive online activities likely to be associated with marked functional impairment, including compulsive online buying, gambling, cybersex, as well as excessive use of online streaming and social media that have addictive, impulsive and/or compulsive elements. 11,13 Age may influence the presentation of PIU and its comorbidities. For example, one study found that attentiondeficit hyperactivity disorder (ADHD) and social anxiety were associated with PIU in young adults; whereas generalised anxiety disorder and obsessive-compulsive disorder (OCD) were associated with PIU in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…Son varios los estudios que vinculan el UPI con el trastorno obsesivo-compulsivo (Derbyshire et al, 2013;Bozkurt et al, 2013;Burnay et al, 2015;Ioannidis et al, 2016;Bernal-Ruiz et al, El metaanálisis muestra un tamaño del efecto significativo a favor del grupo con UPI (p = .0004) (Figura 3), por lo que los dos estudios recogidos confirman que los sujetos con UPI presentan mayores puntajes en los instrumentos que miden el TOC.…”
Section: Trastorno Obsesivo-compulsivo (Toc)unclassified